Fitoterapia como alternativa de desarrollo del turismo de salud, en la provincia de San Martín - Muñoz Chuquizuta, Lili Celestina (2010)
Gentleman of the jury evaluator, as a basic requirement to qualify for the professional title of Bachelor's degree in Tourism Administration, in accordance with the provisions of the regulation of degree and titles of the Faculty Science Economics of the San Martin National University, is fulfilled to present the proyect of the thesis entitled "Phytotherapy as an Altematlve for Health Tourism, DevelopmentIn the San Martin Province ", through its influence on the level of satisfaction of the medical tourist, taking the job as important factors of chaman, the effectiveness of treatments and costs of these treatments, thus increasing the flow of tourists to the province of San Martín through health tourism. The present work is possible to assess the medical tourist in Amazonian folk medicine as a whole, as a full human being: body, mind and spirit that reaches the mental and emotional spheres. emotional - existential, that is why traditional phytotherapy is one of the new alternatives to long boom that will be able to develop a sustainable health tourism and responsible, one Of the alternatives that will allow increased flow of tourists and therefore the development of the province of San Martin, you only need to recognize that we have a diversity of medicinal plants, reliable health centers and shamans gifted scholars with expertise in the cosmos. Health tourism, is allowed to affect the level of satisfaction of the medical tourist through the proper use of medicinal plants as a natural healing alternative. where the completion of treatment will find health, peace, happiness, satisfaction and relationship with nature. Health tourism, through herbal medicine, traditional medicine is one of the fundamental pillars of the identity of Amazonian peoples, ensuring cultural continuity that seeks the protection of traditional use and sacred character of the Ayahuasca ritual, differentiating it Western uses decontextualízed, consumer and commercial purposes. This research work has been developed with a clear, precise and consistent, for the understanding of all people from different cultural and social backgrounds who are interested in assessing the traditional use of medicinal plants as a unique heritage of the San Martin .allowing the conservation and wise use Of medicinal plants by the integration of man with nature. Waiting, for your understanding• of the limitations set out, we appreciate the attention given to this thesis.